Relapse of indurative tuberculosis of the skin of the lower extremities against the background of undiagnosed spontaneously cured pulmonary tuberculosis - Zanna Bialoszycka; Monika Białoszycka; Alisa Pachevska (Journal of Education, Health and Sport)
Introduction. In recent years, there has been a marked increase in the prevalence of cutaneous tuberculosis in Ukraine. Tuberculous lesions of the skin, as a rule, are secondary.